Effect of concrete compressive strength with various natural additives fiber for green environment - Voon, Vincent Boo Chuan (2010)
This study is to investigate the comparisons compressive strength of concrete with egg albumen and coconut fiber as additive materials in concrete composition mixture. Four type of samples are prepared which named by 1% egg albumen (EA), of coconut fiber (CF), 0.5% of egg albumen with 0.5% of coconut fiber (EACF) and Ordinary Portland Cement (OPC) as a control sample (CC). A total 72 cylinders with 150 mm diameter and 300mm height were prepared in four groups according to different mix proportions. The composition mixture rate for sand-cement (s/c) ratio is 2.15, water-cement (wk) is 0.60, aggregate-cement (a/c) is 3.10 and target density is 2400kg/rn 3 . Then, the samples were cured under two curing conditions which were air and water curing for 7th, 14th and 28th days before testing. The compressive strength for concrete with egg albumen was 15. 83MPa, while for the concrete with coconut fiber was 14.78MPa and concrete with both additives materials added was 12.07MPa. The result obtained showed that the concrete with additive material achieved lower compressive strength than the control samples for water curing condition. The samples with 1% of egg albumen showed the higher compressive strength compared to other mixture in both the curing condition. Through the observation, the concrete mixture with egg albumen showed lower early strength gain but is satisfying improvement of strength as the time increased. The study demonstrated that better engineering properties of concrete can be achieved with proper curing condition and type of additive material added.